Progressive Rise in Wound Fabrication at Sialkot (Medical Forum Monthly, 2024)
Objective: to find out the rising patterns and trend of fabrication injuries in respect of demography ,site and nature of injuries.Study Design: Observational / Descriptive studyPlace and Duration of Study: This study was conducted at the Department of Surgery, Allama Iqbal Memorial Teaching Hospital from Jan 2015 to Dec 2017.Materials and Methods: The reports of its examining officer compared with reports of District Standing Board from 2015 to 2017 along with all relevant recordsResults: Total number of cases from 2015 to 2017 are 797, only 304 cases were reexamined by the District Standing Board, The most common weapon used was blunt, head was the most frequently involved site followed by hand, nose, forearm, teeth injury.Conclusion: There is rising trend of fabricated injuries in society because of enmosity, superiority, implicate falsely for internal motives, medical professionals should declare all cases ethically, morally and honestly.